(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Off-label drug use which causes negative, prejudicial and deadly events in pediatric patients, is the starting point to reflect upon the importance of conducting specific clinical trials for children. It is essential to guarantee the development and the following medicine treatment under safety and efficacy conditions. This paper aims at investigating the legal issues linked to clinical trials in pediatric treatment and verifying the effectiveness and forcefulness of traditional juridical categories. It is crucial to think about new possible juridical tools which are able to weigh between children’s right to be involved in scientific development and their need to be protected and safeguarded, in compliance with the best interest of pediatric patients.